Paternidad, filiación y hogar en la interioridad humana según Santo Tomás - Ruiz, Fernández (Sapientia, 2023)
Paternity and filiation are predicated by essence of the divine persons, and from them of human realities by participation. Following the Johannine tradition of the verbumand the Augustinian tradition of the mens, Aquinas approaches the Trinitarian mystery from the generation of the verbum mentisin human interiority, created in the image of God. In this article, we propose, first, to develop the theme of the father-son relationship within the human spirit, in connection with the Neoplatonic notion (De causis; Elementatio Theologica) of reditio ad seipsum(both cognitive and affective: cognitio et amor sui) and verbum cordis. Secondly, we want to focus on a metaphor not often explored in Aquinas's anthropology, namely that of the soul as a house (domus). God Himself can be called a "house" insofar as He dwells in Himself. So too, the human person dwells in himself; this self-presence is the reflective character of his mode of being, which is intimate and recollected. To this house man must return (reditio ad domum) and dwell operatively, guarding and caring for his own interiority and consciousness, being dominus suiipsius.